Parental Spanking and Subsequent Risk for Child Aggression in Father-Involved Families of Young Children - Lee, Shawna J. (2013)
This study examined separate and combined maternal and paternal use of spanking with children at age 3 and children's subsequent aggressive behavior at age 5. The sample was derived from a birth cohort study and included families (n = 923) in which both parents lived with the child at age 3. In this sample, 44% of 3-year-olds were spanked 2 times or more in the past month by either parent or both parents. In separate analyses, being spanked more than twice in the prior month at age 3, by either mother or father, was associated with increased child aggression at 5 years. In combined analyses, there was a dose-response association; the greatest risk for child aggression was reported when both parents spanked more than twice in the prior month (adjusted odds ratio: 2.01; [confidence interval: 1.03-3.94]). Violence prevention initiatives should target and engage mothers and fathers in anticipatory guidance efforts aimed at increasing the use of effective and non-aggressive child discipline techniques and reducing the use of spanking.